Bio-composite Consist of Waste Banana Peel, Egg Shell, Fish Bone, and Titanium Dioxide for Biodegradable Mulching Films - Nik Alnur Auli Nik Yusuf (2023)
The mulching films are agricultural films used to protect crops against weed growth, shield against environmental impacts, conserve water, and fertilise the soil. They are primarily made of polyethelene (PE) because it is affordable and produces high-quality crops, but dumping their waste causes serious problems. The development of biodegradable mulching films from naturally-derived resources could be the solution. In the present study, biodegradable mulching films were produced using biocomposite materials comprised of waste banana peel (WBP) and fillers: eggshell (ES), fishbone (FB), and TiO2. Biocomposite films were prepared according to variations of the glycerol (0, 3, 6, 9, and 12wt%), ES (0, 5, 10, 15, 20wt%), and FB (0, 5, 10, 15, 20wt%) contents and designated as WBP matrix films, WBP-ES, and WBP-FB composites, respectively. The effect of incorporating nanoparticles of TiO2 into WBP-ES and WBP-FB composites had also been evaluated. The WBP matrix films were produced by constantly mixing WBP with glycerol and heated at 80°C for 1 h. The composite films were prepared by the same procedure as the WBP matrix, but with the addition of ES, FB, and TiO2 powders into the WBP matrix. The mixed suspensions were then cast onto an aluminium-nylon mesh mould and pressed to form a composite film. They were observed for morphology, phase identification, the functional group, as well as thermal, physical, and mechanical properties. The composition of raw WBP contains high levels of lignin (44.61%), followed by cellulose (11.25%), and hemicellulose (14.11%) which are commonly found in plant fibre. Plasticizing the WBP matrix with different glycerol amounts has an impact on the WBP matrix film's density, water absorption, thermal stability, and tensile strength. The appropriate level of glycerol with ES and FB loading was 5wt% with ES and FB fillers of 10wt% and 15wt%, respectively. Too much ES and FB content contributes to composite brittleness due to the high agglomeration of dispersed ES and FB particles within the composite. The interfacial bonding between the WBP matrix and FB fillers was weaker, therefore, their density, water absorption, and tensile strength were less than those of the WBP-ES composite. The less agglomerated and homogeneous structure of WBP-ES-TiO2 and WBP-FB-TiO2 composites contributes to improving water-repellent activity and thermal performance. Because the WBP-FB composite has lower adhesion to the matrix and higher porosity, its biodegradability is higher than that of the WBP-ES composite. The biodegradation behaviour of the TiO2-added WBP-ES and WBP-FB composite films was equivalent to that of the WBP-ES and WBP-FB composites. The development of mulching films that decompose naturally is possibly feasible using a biocomposite consisting of WBP, ES, FB, and TiO2. In terms of capabilities, they serve a comparable purpose to PE mulching films and may alleviate the problem posed by plastic mulching films.